2017
DOI: 10.1177/1010428317708546
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing is induced by type I interferon in esophageal squamous cell carcinoma

Abstract: In recent years, abnormal RNA editing has been shown to play an important role in the development of esophageal squamous cell carcinoma, as such abnormal editing is catalyzed by ADAR (adenosine deaminases acting on RNA). However, the regulatory mechanism of ADAR1 in esophageal squamous cell carcinomas remains largely unknown. In this study, we investigated ADAR1 expression and its association with RNA editing in esophageal squamous cell carcinomas. RNA sequencing applied to esophageal squamous cell carcinoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A venn diagram was constructed to intersect the two sets of results, identifying a total of 97 genes associated with OS. A number of genes were found to have prognostic value for patients with ESCC, including FOS (24), Adenosine Deaminase RNA Specific (25,26), Karyopherin Subunit α 2 (27) and Translocator protein (28). These genes were enriched in a number of signaling pathways, including DNA replication, protein processing in endoplasmic reticulum and influenza, as demonstrated using KEGG analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A venn diagram was constructed to intersect the two sets of results, identifying a total of 97 genes associated with OS. A number of genes were found to have prognostic value for patients with ESCC, including FOS (24), Adenosine Deaminase RNA Specific (25,26), Karyopherin Subunit α 2 (27) and Translocator protein (28). These genes were enriched in a number of signaling pathways, including DNA replication, protein processing in endoplasmic reticulum and influenza, as demonstrated using KEGG analysis.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of ADAR1 in cancers may be caused by ADAR gene amplification, and interferon response due to chronic inflammation (Fumagalli et al, 2015). Furthermore, JAK–STAT signaling pathway activation has been associated with increased ADAR1 levels in malignancies (Zhang et al, 2017; Zipeto et al, 2016). A previous study revealed that the increased JAK2 signaling and breakpoint cluster region‐Abelson murine leukemia 1 amplification activate ADAR1 expression in blast crisis chronic myeloid leukemia progenitors (Zipeto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…AZIN1 ‐dependent editing, together with FLNB A‐to‐I edition, is also involved in the pathogenesis of ESCC (Qin et al, 2014). Interestingly, type I IFNs and their associated JAK/STAT pathways, up‐regulate ADAR1 expression resulting in aberrant A‐to‐I editing process in ESCC (Zhang, Chen, Tang, et al, 2017). In contrast, a tumour suppressor role for ADAR2 has been described and down‐regulation of ADAR2 enzyme has been linked to ESCC progression.…”
Section: De‐regulated Epitranscriptome In Cancermentioning
confidence: 99%